PERENCANAAN KOMUNIKASI POLITIK PENYELENGGARA PEMILU DALAM MENGHADAPI PEMILU SERENTAK 2024 DI KABUPATEN TUBAN - Nibrosu Rohid; Eka Wisnu Wardhana; Abdul Warits (Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The General Elections in Tuban Regency which have been held so far have been running safely and peacefully. This can be shown from the existence of violations that do not lead to criminal. This cannot be separated from the Political Communication that has been implemented by the election organizers in Tuban Regency. Research that takes the theme of Political Communication Planning for Election Organizers in the face of the 2024 General Election in Tuban Regency is a qualitative research type. Using interview data collection methods and document studies which are then reduced, presented and conclusions drawn. The results showed that the Political Communication Planning carried out by the election organizers in Tuban Regency was divided into three, is Coordination, Voter Education and Dissemination of Information about the 2024 Election. The methods used in political communication were online and offline. In addition, the use of social media to convey information about the 2024 General Election is also carried out optimally